The Relationship between Well-being and Risk of Wondering among Elderly with Dementia in Mental Health Hospital, Dr. Radjiman Wediodiningrat Lawang, Malang - Amalia Kusumaningsih; Ah Yusuf; AV Sri Suhardiningsih (Alta Dharma Publisher, 2020)
Dementia is a syndrome in the form of decreased cognitive function. Wandering is a neuropsychiatric symptom that has an impact on mortality rates which are indicators of achievement of subjective well-being. The study aimed to determine relationship between subjective well-being and risk of wandering among elderly with dementia. A quasi-experimental study, one group pre-post test design was applied in this study, we recruited 34 elderlies and their caregivers using the purposive method. The result showed that there is positive effect of social leisure activity in reducing wandering risk (p=0,000) and increasing subjective well-being (p=0,000). Subjective well-being has a significant correlation with the risk of wandering at the post-test (p=0,000). The result given between characteristic’s elderly and subjective well-being showed p-value less than 0,05 excepted on neuropsychiatric symptoms. Subjective well-being correlation with decreased risk of wandering by providing regular physical activity